Level of informatization of public administration services in the voivodeships of Poland in 2014-2022 - Kuzionko - Ochrymiuk, Ewa; Szanter, Renata; Niedzielski, Piotr (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
The purpose of the study is to assess the level of differentiation of informatization of public administration services in the voivodeships in Poland. Research methodology: The study involved the selection of quantitative variables depicting the level of informatization of public administration in the voivodeships in Poland. The selected variables were analyzed using the TOPSIS linear ordering method. The analysis was based on the data of the Central Statistical Office for the years 2014-2022. The results of the study showed significant disproportions between individual voivodeships, where the voivodeships with the highest level of public administration informatization were the mazowieckie and Pomeranian voivodeships whereas voivodeships with the lowest level of public administration informatization were podkarpackie, opolskie and świętokrzyskie